Display of Free-range Chicken Semen After Supplementation of Phylanthus Niruri Herbal Extract and Kaffir Lime Leaf Extract (Citrus Hystrix D. C) - Heru Suripta; Puji Astuti; Ina Nurtanti; Dimas Fajar Nugroho (Postgraduate, University of Mataram, 2025)
This study was conducted to examine the supplementation of green meniran herb extract (Phylanthus niruri L) and kaffir lime leaf extract (Cytrus hystrix D. C.) on the appearance of free-range chicken semen. The study was conducted using a completely random design of unidirectional patterns, using 24 male free-range chickens aged about one year with an average weight of 1.8 kg with eight treatments, three replicates each. Each replicate consisted of 1 chicken. Basal feed uses BR-1 chicken feed produced by PT. Japfa Comfeed Indonesia Tbk. After 1 week of basal feeding, chicken sperm was taken and tested for control (H-0), then began to be treated with testosterone supplementation, as a positive control, meniran extract, kaffir lime leaf extract, or a mixture thereof. The following semen collection is carried out after 1 week of treatment. Semen collection is carried out every 3 days with five intakes. This study concludes that the supplementation of green meniran herb extract and kaffir lime leaf extract or a combination thereof, macroscopic, does not change the appearance of free-range chicken semen, both volume, color, consistent odor, and pH of semen, but microscopic significantly increase sperm concentration, motility, and Viability. There was no synergy between green meniran herb extract and kaffir lime leaf extract on the appearance of chicken semen.